Impact on HIV-1 RNA Levels and Antibody Responses Following SARS-CoV-2 Vaccination in HIV-Infected Individuals - Portillo, Vera; Fedeli, Chiara; Ustero Alonso, Pilar; Petignat, Ianis; Mereles Costa, Ellen Cristina; Sulstarova, Adi; Jaksic, Cyril; Yerly, Sabine; Calmy, Alexandra (Frontiers in Immunology, 2022)
This study aims to assess the immunological response and impact on virological control of the mRNA vaccines for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) among people living with HIV (PLWH). In this single-centre observational study, all PLWH were offered vaccination with mRNA1273 or BNT162b2. Both anti-N and anti-S1-receptor binding domain (RBD) antibodies were measured together with HIV-1 RNA levels after the first dose (M0) and then at 1 (M1), 2 (M2) and 6 (M6) months later. A total of 131 individuals (median age: 54 years [IQR: 47.0-60.5]; male: 70.2%; median baseline CD4 T-cell: 602 /µl [IQR 445.0-825.5]; median nadir CD4 T-cells 223/µl [IQR 111.0-330.0]) were included. All participants were positive for anti-RBD antibodies at 30 days, 60 days and 6 months after the first dose, with no statistical difference between those with HIV-1 RNA below or >20 copies m/L. HIV-1 RNA data were collected for 128 patients at baseline and 30 days after the first dose; for 124 individuals, 30 days after the second dose; and for 83 patients, 6 months after the first dose. Nineteen (14.8%) of 128 had detectable HIV-1 RNA (>20 copies/ml) at M0, 13/128 (10.2%) at M1 (among which 5 were newly detectable), 15/124 (12.1%) at M2 (among which 5 were newly detectable), and 8/83 (9.6%) at M6. No serious adverse effects were reported. All participants elicited antibodies after two doses of mRNA vaccines, with only a minor impact on HIV-1 RNA levels over a 6-month period.